Functional expression and pharmaceutical efficacy of cardiac-specific ion channels in human embryonic stem cell-derived cardiomyocytes. Issue 1 (December 2017) - Kim, Han Sol; Yoon, Jung; Li, Hongliang; Jeong, Geun Ok; Park, Jin Ju; Shin, Sung; Jang, Il; Kim, Jae Ho; Park, Won
Abstract Cardiomyocytes differentiated from human pluripotent stem cells provide promising tools for screening of cardiotoxic drugs. For evaluation of human pluripotent stem cell-derived cardiomyocytes for cardiotoxicity test, in the present study, human embryonic stem cells (hESCs) were differentiated to cardiomyocytes, followed by metabolic selection to enrich the differentiated cardiomyocytes. The highly purified hESC-derived cardiomyocytes (hESC-CMs) expressed several cardiomyocyte-specific markers including cTnT, MLC2a, and α-SA, but not pluripotency markers, such as OCT4 and NANOG. Patch clamp technique and RT-PCR revealed the expression of cardiomyocyte-specific Na+, Ca2+, and K+ channels and cardiac action potential in hESC-CMs. To explore the potential use of hESC-CMs as functional cardiomyocytes for drug discovery and cardiotoxicity screening, we examined the effects of bisindolylmaleimide (BIM) (I), which inhibits native cardiac Ca2+ channels, on the Ca2+ channel activity of hESC-CMs. We observed a similar response for the BIM (I)-induced modulation of Ca2+ channels between hESC-CMs and native cardiomyocytes throughL -type Ca2+ channel current. These results suggest that hESC-CMs can be useful for evaluation of pharmaceutical efficacy and safety of novel drug candidate in cardiac research.